Estrogen treatment reduced oxalate transporting activity and enhanced migration through the involvement of SLC26A6 in lung cancer cells. (August 2022) - Lee, Dongun; Lee, Peter Chang-Whan; Hong, Jeong Hee; Shin, Dong Min
Abstracts: Estrogen therapy has used to prevent bone loss in postmenopausal women. Although therapeutically enhanced estrogen levels have been suggested, patients are exposed to greater risks of nephrolithiasis and cancer. It has been known that oxalate or bicarbonate transporter SLC26A6 is involved in oxalate homeostasis and its deletion results in kidney stone formation and addressed that patients with kidney stones possess higher cancer risk. Thus, the mechanism of the interaction between estrogen and SLC26A6 and the effect of SLC26A6 on cancer cells should be elucidated. In this study, we investigated whether β-estradiol treatment modulates SLC26A6 expression and its bicarbonate or oxalate transporting activity and affects the proliferative and migratory ability of A549 cells. The β-estradiol stimulation attenuated oxalate or bicarbonate transporting activities through SLC26A6. Knockdown of SLC26A6 reduced transporter activity whereas enhanced cellular migration. β-estradiol-mediated cellular migration was independent of SLC26A6 transporter activity, whereas enhanced SLC26A6 expression attenuated cellular migration even in the presence of β-estradiol treatment. These results indicate β-estradiol treatment enhances cancer cell migration and dysregulates oxalate transport by inhibiting SLC26A6 activity, suggesting reduced oxalate transporting activity may involve in the oxalate homeostasis. Highlights: The treatment of β-estradiol attenuates oxalate transporting activity. SLC26A6 expression involves in the inhibition of cellular migration. The negative effect of estrogen on activity of chloride oxalate exchanger SLC26A6 in lung cancer cells reflects modulation of estrogen on oxalate homeostasis of lung cancer cell.